A rare case of tonsillar mucoepidermoid carcinoma - Charbél Talani; Karin Frånlund; Crina Unguras (Acta Oto-Laryngologica Case Reports, 2023)
AbstractMucoepidermoid carcinoma (MEC) is one of the most common histological malignant salivary gland tumors, it is most frequently diagnosed in the parotid gland. MEC is also diagnosed in the intra oral minor salivary glands. Only a few cases of tonsillar MEC have been reported. We present a rare case of mucoepidermoid carcinoma arising from the left pharyngeal tonsil. This case report shows that it is important to perform tonsillectomy when discovering neck metastasis of salivary gland tumors with unknown primary.